RADIOGRAPHIC FINDINGS OF TEMPOROMANDIBULAR JOINT OSSEOUS CHANGES USING CONE-BEAM COMPUTED TOMOGRAPHY IN A SAUDI POPULATION: A RETROSPECTIVE STUDY - Alalawi, Waleed Abdulhadi; Kolarkodi, Shaul Hameed; Alotaibi, Khalid; Altwaijri, Abdulrahman; Alotaiby, Faraj (Journal of Ayub Medical College Abbottabad, 2025)
Background: The temporomandibular joint (TMJ) is a complex synovial articulation that plays a critical role in mastication, speech, and mandibular movements. Pathologies affecting the TMJ, such as internal derangement, osteoarthritis, and degenerative bone changes, can significantly impair function and quality of life. Objectives were to evaluate the prevalence and pattern of osseous changes in the temporomandibular joint (TMJ) using cone-beam computed tomography (CBCT) in a Saudi population, with emphasis on diagnostic and surgical relevance. Methods: This retrospective study was conducted in the Department of Diagnostic Sciences, Qassim University, Saudi Arabia, and included 414 bilateral CBCT scans obtained between January 2020 and December 2024. Scans were evaluated for degenerative bony changes such as condylar flattening, erosion, osteophytes, subchondral sclerosis, and cysts. Two experienced radiologists performed independent assessments, and inter-examiner reliability was calculated. Demographic associations were analyzed using Chi-square and ANOVA tests, with significance set at p<0.05. Results: Of the 414 subjects, 260 (62.8%) were male and 154 (37.2%) were female. Condylar flattening was the most frequent pathology, observed in 10.63% of right and 9.90% of left TMJs, followed by erosion and subchondral cysts. A total of 73.7% of cases exhibited radiographic abnormalities. Age was significantly associated with the presence of TMJ pathologies (p<0.01), particularly in individuals aged 40–60 years. No statistically significant association was found between gender and TMJ degeneration. Conclusions: cone-beam computed tomography effectively detects subtle and early-stage TMJ osseous changes, with flattening, erosion, and cystic degeneration being the most prevalent findings. The strong age-related pattern of TMJ degeneration supports the need for early radiographic screening, especially in middle-aged adults. From a surgical perspective, CBCT imaging plays a vital role in preoperative planning, aiding in the decision-making process for conservative versus surgical interventions.